Od prośby do nakazu. Rada w "Poradniku domowym" Jacka Dziadkowskiego = From request to order. Advice in "Poradnik domowy" ("Home guidance") by Jacek Dziadkowski - Jurewicz-Nowak, Magdalena; Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains a pragma-linguistic analysis of "advice" and other directive act`s established in the "Home guidance" by Jacek Dziarkowski (1819). The aim of this study is to show the contextual conditions of the speech act interpretation. The source represents the utility genre with a teaching function. The pieces of "advice" selected from it illustrate urging to take some actions in order to achieve social benefits.
Keywords: analiza pragmalingwistyczna; akt mowy; przewodnik; perswazja; pragma-linguistic analysis; speech act; advice; guidebook; persuasion